2012
DOI: 10.1111/j.1365-2230.2012.04435.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological patterns of perniosis, and its association with systemic disorder

Abstract: Perniosis is not rare in children, but patients with secondary perniosis are more likely to be older. In terms of underlying systemic disorder, advanced age and male gender may be important demographic features. Measurement of cryoglobulin levels in the initial laboratory investigations of patients with perniosis is not necessary. Persistence beyond the cold seasons, and presence of photosensitivity, hypergammaglobulinaemia and rheumatoid factor may be useful in differentiating between idiopathic and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
50
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 13 publications
6
50
0
5
Order By: Relevance
“…13 Consistent with this, Takci et al reported that the mean age of the group with secondary chilblains was significantly higher than the group with primary chilblains. 9 The occurrence of chilblains in children has been stated to be uncommon by Gardinal-Galera et al 12 but Takci et al 9 reported that 49% of patients in their study were aged between 0-18. Pediatric patients were present in our study as well.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…13 Consistent with this, Takci et al reported that the mean age of the group with secondary chilblains was significantly higher than the group with primary chilblains. 9 The occurrence of chilblains in children has been stated to be uncommon by Gardinal-Galera et al 12 but Takci et al 9 reported that 49% of patients in their study were aged between 0-18. Pediatric patients were present in our study as well.…”
Section: Discussionmentioning
confidence: 92%
“…9,10 The terms idiopathic or primary have been used to describe chilblains when there is no clinical and/or laboratory sign related to connective tissue disease and other underlying disorder. Atypical chilblains was termed by Viguier et al 10 to classify patients showing one to three of the revised criteria of the American College of Rheumatology (ACR) for systemic lupus erythematosus and/or any clinical or laboratory manifestations of connective tissue diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations